ASPEK HUKUM PENGGUNAAN TEKNOLOGI INFORMASI DALAM WAKAF UANG DI INDONESIA (UIN Sunan Kudus, 2014)
Waqf money more effectively and become the trend of worship today, becausethe endowment money, the money is used as capital, then distribute the profitsas endowments. However, the process of distribution of cash waqf requireswakif must transfer money to Nazhir wakafnya wakafnya that money can bedistributed in the manner intended. Therefore, may assume a very importantrole of information technology to simplify all matters in the field of bankingaffairs, including through electronic media. This will be analyzed in termsof the legal aspects of the use of information technology in the waqf moneyas protection and legal protection. Waqf money is one of the productiveendowments. Endowments productive is a gift in the form of something thatcan be cultivated or rotated for the good and benefit of the people. The shapecan be either cash or securities. Waqf money distribution process requireswakif must transfer money to Nazhir wakafnya wakafnya that money can bedistributed in the manner intended. The use of electronic media in terms ofthe distribution of money endowments that we can see the setting in Act No.11 of 2008 on Information and Electronic Transactions (UU ITE) in article1, paragraph (2) which states that: “Electronic transactions are legal actperformed by using a computer, computer network and / or other electronicmedia. “. Regarding the placement money waqf stipulated in Article 25(d) of Government Regulation (PP) No. 42 of 2006 on the Implementationof Law No. 41 of 2004 on endowments. to facilitate the delivery of moneywaqf is done by transferring money from the endowment wakif to depositaccounts which have been provided by Nazhir through the bank. Along withthe development of information technology as well as to facilitate all mattersincluding the business banking sector use of electronic media such as internet,ATM, credit card or SMS banking included in conveying the waqf money.